A study on factors that affect the level of awareness among employees in HSE Resources Sdn. Bhd. for their future personal financial planning / Nurhidayah Mohd Ariff and Nur Asyikin Md. Jalil - Mohd Ariff, Nurhidayah; Md. Jalil, Nur Asyikin (Faculty of Business and Management, 2014)
Personal finance is the application of the principles of finance to the monetary decisions of an individual or family unit. It addresses the ways in which individuals or families obtain, budget, save, and spend monetary resources over time, taking into account various financial risks and future life events. Components of personal finance might include savings accounts, credit cards and consumer loans, retirement planning, investments and insurance policies and income tax management. The main purpose of this study is to study the factors that affect the level of awareness among employees in HSE Resources Sdn. Bhd. for their future personal financial planning. This study suggests that the factors that influence the level of emplyee’s awareness are family structure, socioeconomics, financial literacy and peer influence. The study follows exploratory research as medium to study the factors that affect the level of awareness among employees on their future personal financial planning. A set of questionnaires with 6 sections and 100 questionnaires were distributed to the employees in HSE Resources Sdn Bhd. Reliability test, frequency test, descriptive analysis, correlation analysisi and regression has been chosen as the method to find the result. The findings indicate that the financial literacy is the most factors that affect the level of awareness among employees in HSE Resources Sdn Bhd for their future personal financial planning than family structure, socioeconomics and peer influence.